Distribution and Numbers of the Kaminuriak Caribou Herd in March and April, 1977 - Thompson, D.C.; Fischer, C.A. (ARCTIC, 1979)
The distribution and abundance of the Kaminuriak caribou herd were documented through an aerial survey conducted in March and April 1977. It appears that the herd altered its traditional migration patterns and abandoned its southern wintering grounds in this year at least. The size of the herd was estimated at 30,770 animals - a significant decrease from the 63,000 animals found in 1968. Available data, although limited, suggests that the maximum allowable harvest of 5% of the herd has been exceeded in recent years. Although the possibility exists that some Kaminuriak caribou may have dispersed northward, it is considered most likely that the decline in the size of the herd is the result of overharvesting.